Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:
(1) For both \(Y=0.3, Z=0.7\) and \(Y=0.7, Z=0.3\) we have \(Y+Z=1\). Insufficient
(1) For both \(Y=0.3, Z=0.7\) or \(Y=0.3, Z=-0.7\) we have \(Y^2 < Z^2\). Insufficient
(1)+(2) From Statement (1) \(Z=1-Y\), and put in Statement (2): \(Y^2 < (1-Y)^2\) \(Y^2 < 1-2Y+Y^2\) \(2Y< 1\) \(Y<1/2\) Therefore, \(-Y>-1/2\) and \(1-Y>1-1/2\) and \(Z=1-Y>1/2\). Hence, \(Y<Z\). Sufficient
The correct answer is C.
I'm happy, if I make math for you slightly clearer And yes, I like kudos:)
Statement 1 : y+z = 1 , This can be possible in different cases : Case 1 : 0<y<1 and 0<z<1 Case 2 : y>=1 and as Z = 1 - y so z<=0 Case 3 : Z>=1 and as y = 1-z so y<=0 As we can't conclude whether y>z or y<z, statement 1 is not sufficient
Statement 2 : y^2 < z^2 , again which is possible in many cases case 1 : z>y>0 case 2 : z>0>y and z>|y| case 3 : y>0>z and y<|z| case 4 : 0>y>z As we can't conclude whether y>z or y<z, statement 2 is also not sufficient
By combining two statements and observing all the cases from both statements we can eliminate case 4 and case 3 from statement 2 as they violate the condition y + z = 1 from statement 1. So from the remaining cases which satisfy both statements we can clearly observe z>y . Hence we can say yes y<z.
(1) y + z = 1. The sum of two numbers is 1. Obviously from this info we cannot say which one is bigger. Not sufficient.
(2) y^2 < z^2 --> take the square root from both sides (we can safely do that since we know that both sides are non-negative): |y| < |z| --> z is farther from 0 than y is. Not sufficient.
(1)+(2) From (2): (y - z)(y + z) < 0. This implies that y - z and y + z have opposite signs. Since we know from (1) that y + z is positive, then y - z must be negative: y - z < 0 --> y < z. Sufficient.
1) y + z = 1: Scenario 1 - y= 0.3, z = 0.7, y + z = 1 and y < z; Scenario 2 - when y = 4, z = -3, y > z. Hence, not sufficient.
2) \(y^2\) < \(z^2\), From this statement, we can only that absolute value of y is greater than absolute value of z. y =-4 and z = 5, and \(y^2\) = 16 and \(z^2\) = 25, \(y^2\) < \(z^2\), but z > y. Not sufficient.
Consider both statements together. when both y and z are positive, y< z as \(y^2\) < \(z^2\). when only 1 of y and z are positive, y + z = 1 -> y = 1 -z . If y is negative, z has to be positive, so y < z when only 1 of y and z are positive, y + z = 1 -> y = 1 -z , if y is positive, z has to negative. If y = 4, z = -3. If y = 5, z = -4. If y=6, z=-5. As you can see |y| > |z|, but from statement 2, \(y^2\) < \(z^2\) or |y| < |z|. So, we can never have a scenario where y is positive and z is negative. Note that y and z both cannot be negative as y + z = 1.